XOR-FREE Implementation of Convolutional Encoder for Reconfigurable Hardware. (23rd February 2016) - Purohit, Gaurav; Raju, Kota Solomon; Chaubey, Vinod Kumar
Abstract : This paper presents a novel XOR-FREE algorithm to implement the convolutional encoder using reconfigurable hardware. The approach completely removes the XOR processing of a chosen nonsystematic, feedforward generator polynomial of larger constraint length. The hardware (HW) implementation of new architecture uses Lookup Table (LUT) for storing the parity bits. The design implements architectural reconfigurability by modifying the generator polynomial of the same constraint length and code rate to reduce the design complexity. The proposed architecture reduces the dynamic power up to 30% and improves the hardware cost and propagation delay up to 20% and 32%, respectively. The performance of the proposed architecture is validated in MATLAB Simulink and tested on Zynq-7 series FPGA.